Penerapan Metode Pembelajaran Student Teams Achievement Divisions (STAD) Untuk Meningkatkan Keaktifan Belajar Pada Mata Pelajaran Ilmu Pengetahuan Sosial (IPS) Siswa Kelas VIII Di Madrasah Tsanawiyah Negeri Susukan - Ainul Khusnayati, Silfi; , Drs. Sami'an, M.M (2017)
The aim to be achieved in this research is to improve learning activeness of students class VIII in Madrasah Tsanawiyah Negeri Susukan through the use of methode type STAD. Students class VIII D as the recipient and the theacher as a giver of action. Data collection methods used are observation, interview, and documentation. Data analysis techniques used are data reduction, data presentation, and conclution. From the data collected during the study with two cycles of data obtained follows : 1) students who read or understand the problems contained in the student worksheet (LKS) as much as 27,02% increased to 100%, 2) students who solve problems or find answers as much as 24,32% increase to 75,67%, 3) students who expressed opinion as much as 13,51% become 75,67%, 4) students who discuss or ask among students and teachers as much as 40,54% increased to 100%. Based on the result of research can be concluded that STAD learning method can improve learning activeness of students on IPS.